2015
DOI: 10.1021/acs.jpca.5b07509
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Detection of Benzocyclopropenyl

Abstract: The gas phase detection of benzocyclopropenyl is reported. In this aromatic resonance stabilized radical, a large angular strain is present due to a three-membered ring annelated to a benzene. The resonant two-color two-photon ionization technique is used to record the D1(2A2) ← D0(2B1) electronic transition of this radical after the in situ synthesis in a discharge source. The spectrum features absorptions up to 3300 cm–1 above the origin band at 19 305 cm–1. Benzocyclopropenyl is possibly the major product o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Recent laser spectroscopic investigations report many such radicals in supersonic jets (Tsuge et al 2006;Reilly et al 2008Reilly et al , 2009aReilly et al , 2009bTroy et al 2009Troy et al , 2011Troy et al , 2014Sebree et al 2010aSebree et al , 2010bSebree et al , 2011Chalyavi et al 2011Chalyavi et al , 2012Kidwell et al 2013Kidwell et al , 2014O'Connor et al 2013O'Connor et al , 2015Maity et al 2015aMaity et al , 2015b. Several of them could be recognized among the discharge products of the (partly decomposed) 1, 6-heptadiyne precursor, e.g., cis-and trans-1-vinylpropargyl C 5 H 5 (Reilly et al 2009b), 1, 4-pentadienyl C 5 H 7 , benzocyclopropenyl C 7 H 5 (Maity et al 2015b), benzyl C 7 H 7 (Foster & Miller 1989), 1-phenylpropargyl C 9 H 7 (Reilly et al 2009a), and 1-indanyl C 9 H 9 Maity et al 2015a).  Furthermore, we observed the triplet chains HC 5 H and HC 7 H (Steglich et al 2015;Ding et al 2003), as well as previously unidentified species on masses corresponding to C 7 H 5 , C 7 H 7 , C 7 H 9 , C 8 H 9 , C 9 H 5 , and C 9 H 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent laser spectroscopic investigations report many such radicals in supersonic jets (Tsuge et al 2006;Reilly et al 2008Reilly et al , 2009aReilly et al , 2009bTroy et al 2009Troy et al , 2011Troy et al , 2014Sebree et al 2010aSebree et al , 2010bSebree et al , 2011Chalyavi et al 2011Chalyavi et al , 2012Kidwell et al 2013Kidwell et al , 2014O'Connor et al 2013O'Connor et al , 2015Maity et al 2015aMaity et al , 2015b. Several of them could be recognized among the discharge products of the (partly decomposed) 1, 6-heptadiyne precursor, e.g., cis-and trans-1-vinylpropargyl C 5 H 5 (Reilly et al 2009b), 1, 4-pentadienyl C 5 H 7 , benzocyclopropenyl C 7 H 5 (Maity et al 2015b), benzyl C 7 H 7 (Foster & Miller 1989), 1-phenylpropargyl C 9 H 7 (Reilly et al 2009a), and 1-indanyl C 9 H 9 Maity et al 2015a).  Furthermore, we observed the triplet chains HC 5 H and HC 7 H (Steglich et al 2015;Ding et al 2003), as well as previously unidentified species on masses corresponding to C 7 H 5 , C 7 H 7 , C 7 H 9 , C 8 H 9 , C 9 H 5 , and C 9 H 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In our studies of the electronic spectra of hydrocarbon radicals-also of interest as intermediates in combustion processes-we obtained spectra of a number of species of the type C n H m (e.g., Maity et al 2015aMaity et al , 2015b, i.e., carbonaceous molecules containing more than two or three hydrogens. Some of these fit into the category sought by Oka's work: a prolate structure and a small number of heavy atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of such moderate size carbon clusters are of importance in astronomical context [32]. For instance, the structural conformation of partially hydrogenated C 7 and C 9 neutrals as well as ions are proposed as the possible carriers of some weak diffuse interstellar bands(DIBs) in the ISM [33,34]. Steglich et al calculated the most stable structures of C 9 H 5 radicals and also recorded their emission bands to identify the possible carriers of these weak bands.…”
Section: + Ch + Ch + 2 Coincidencementioning
confidence: 99%
“…The formation of such neutral or ionic hydrocarbon species is of importance in the astronomical context [37]. For instance, the structural conformations of partially hydrogenated C 7 and C 9 neutrals as well as ions are proposed as the possible carriers of some weak diffuse interstellar bands in the ISM [38,39]. Steglich et al [38] computationally identified stable structures of C 9 H 5 radicals, which are found to feature visible absorption bands that coincide with a few very weak diffuse interstellar bands.…”
Section: Ch + 3 Coincidencementioning
confidence: 99%